2008
DOI: 10.1158/1055-9965.epi-08-0507
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Array Analysis of Preoperative and Postoperative Saliva DNA in Oral Cancer Patients

Abstract: Purpose: To perform methylation array analysis of 807 cancer-associated genes using tissue and saliva of oral squamous cell carcinoma (OSCC) patients with the objective of identifying highly methylated gene loci that hold diagnostic and predictive value as a biomarker. Experimental Design: We did the methylation array on DNA extracted from preoperative saliva, postoperative saliva, and tissue of 13 patients with OSCC, and saliva of 10 normal subjects. We identified sites that were highly methylated in the tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 22 publications
1
90
0
1
Order By: Relevance
“…In a recent study, Jithesh et al 39 also employed the same array and suggested that EPHA5, GSTM2, HS3ST2, MME, MT1A, MYOD1, NPY, and PENK are potential biomarkers for detecting oral cancer, as in the present study. The only triple-hit gene among the studies of Viet et al, 10 Jithesh et al, 39 and ourselves was EPHA5. In addition, Nagata et al 40 reported that the aberrant methylation of a combination of ECAD, TMEFF2, RARb, and MGMT from rinse samples can detect OSCC with a sensitivity and specificity of >90% by using noninvasive methods to retrieve samples and a different methylation platform.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…In a recent study, Jithesh et al 39 also employed the same array and suggested that EPHA5, GSTM2, HS3ST2, MME, MT1A, MYOD1, NPY, and PENK are potential biomarkers for detecting oral cancer, as in the present study. The only triple-hit gene among the studies of Viet et al, 10 Jithesh et al, 39 and ourselves was EPHA5. In addition, Nagata et al 40 reported that the aberrant methylation of a combination of ECAD, TMEFF2, RARb, and MGMT from rinse samples can detect OSCC with a sensitivity and specificity of >90% by using noninvasive methods to retrieve samples and a different methylation platform.…”
mentioning
confidence: 73%
“…Several methods of determining the occurrence of promoter methylation have been described in the literature, including methylation-specific PCR (MSP), combined bisulfite restriction analysis, bisulfite sequencing assay, pyrosequencing methylation assay, and microarray-based methylation analysis; the overwhelming majority of published data were obtained using the MSP method. Literature reviews [10][11][12] have revealed a wide variation in the reported sensitivity and specificity for this method, ranging from 30% to 90%. Given the limited number of CpG sites detected by MSP and the inconsistent results obtained using this method, we developed a diagnostic tool for OSCC using a high-throughput, quantitative methylation platform-the Illumina GoldenGate Methylation Array-to allow a more comprehensive profiling of DNA methylation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor-specific DNA in saliva could also be used as biomarker for oral cancer [45]. Methylation array of salivary DNA was supported as an effective biomarker for early detection of oral cancer [46]. Hypermethylation on the promoter of DNA in specific gene All the biomarkers were significantly altered in oral cancer and found to be useful as a supportive tool for diagnosis, prognosis and post-operative monitoring.…”
Section: Salivary Genomics and Proteomics Biomarkers In Oral Cancermentioning
confidence: 99%
“…An assay was developed that could rapidly quantify the promoter hypermethylation of the gene of interest and could potentially be applied into a clinical setting. [46,48] Salivary IL-8 mRNA and protein EC sensor was developed with multiplexing biomarker detection for salivary diagnostics. IL-8 mRNA and IL-8 protein levels measured by the EC sensors showed significant differences between oral cancer patients and controls.…”
Section: M2bp Mrp14mentioning
confidence: 99%